Analysis and Compilation of Normal Map Generation Techniques for Pixel Art - Moreira, Rodrigo; Coutinho, Flávio; Chaimowicz, Luiz (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais do XXI Simpósio Brasileiro de Jogos e Entretenimento Digital, 2022)
Pixel art is a popular artistic style adopted in the gaming industry, and nowadays, it is often accompanied by modern rendering techniques. One example is dynamic lighting for the game sprites, for which normal mapping defines how the light interacts with the material represented by each pixel. Although there are different methods to generate normal maps for 3D games, applying them for pixel art may not yield correct results due to the style specificities. Therefore, this work compiles different normal map generation methods and study their applicability for pixel art, reducing the scarcity of existing material on the techniques and contributing to a qualitative analysis of the behavior of these methods in different case studies.